The International Economic Environment and the Philippine Economy - Leilanie Q. Basilio; Ponciano Jr. S. Intal (Philippine Institute for Development Studies (PIDS), 1998)
The Philippines is in the midst of a region where its neighboring countries are on their way to greater economic openness and deeper economic integration. The country has followed suit and is in fact a member of various international trade organizations. This paper focuses on two important developments in the international economic environment facing the country today and tomorrow: openness, integration and globalization and the rise of China and Asia Pacific.
Keywords: 330; globalization; economic openness; savings mobilization; regional integration